The center points , so the ones with a full line divide by 2
Answer:
![\boxed{\bold{\frac{m^2}{\left(m+n\right)\left(m-n\right)}}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbold%7B%5Cfrac%7Bm%5E2%7D%7B%5Cleft%28m%2Bn%5Cright%29%5Cleft%28m-n%5Cright%29%7D%7D%7D)
Step-by-step explanation:
Factor ![\bold{m^2-n^2}](https://tex.z-dn.net/?f=%5Cbold%7Bm%5E2-n%5E2%7D)
![\bold{\left(m+n\right)\left(m-n\right)}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cleft%28m%2Bn%5Cright%29%5Cleft%28m-n%5Cright%29%7D)
Rewrite Equation
![\bold{\frac{m^2}{\left(m+n\right)\left(m-n\right)}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cfrac%7Bm%5E2%7D%7B%5Cleft%28m%2Bn%5Cright%29%5Cleft%28m-n%5Cright%29%7D%7D)
The inverse of function f(x) = 9x+7 is f-1(x) = x/9 - 7/9
<h3>How to determine the inverse of the function?</h3>
The function is given as:
f(x) = 9x + 7
Express f(x) as y
y = 9x + 7
Swap the positions of x and y in the above equation
x = 9y + 7
Subtract 7 from both sides
9y = x - 7
Divide through by 9
y = x/9 - 7/9
Express as an inverse function
f-1(x) = x/9 - 7/9
Hence, the inverse of function f(x) = 9x+7 is f-1(x) = x/9 - 7/9
Read more about inverse functions at:
brainly.com/question/14391067
#SPJ1
Multiply the number together ....
(-3x)4 = -12x